ELECTRONIC HUMAN RESOURCE MANAGEMENT : INOVASI PENGELOLAAN SUMBER DAYA MANUSIA DALAM ORGANISASI (ANALISIS PENERAPAN E-HRM PADA PT TELKOM WILAYAH KUPANG – NTT) - Klaasvakumok Jehezkielomi Kamuri (Journal of Management Small and Medium Enterprises (SMEs), 2017)
Key to the success of an organization is the human resources (HR). The central role of human resourcesbecome the main driving force for the organization to respond to the various challenges faced. Someorganizations attempt a variety of ways to improve the quality of its human resources by using theinformation and communication technology development called Electronic Human Resource Management(EHRM). The purpose of this research is to analyze the application of EHRM conducted by PT. TelkomKupang region. Interviewees on this research was the head of SAS Asman, head of human resources andthe Supporting Business, JOM IT Witel, and several employees of PT Telkom Kupang region. Theapproach used in this study is a qualitative descriptive study which aims to give you an idea that becamethe focus of attention of this research. The results of this research show the application of EHRM by PTTelkom Kupang region NTT brings changes and progress in working, improves employees skills, ultimatelyimproves the quality of work and quality of service.Keywords: Human Resources, The Electronic Human Resource Management